When local virtues meet national policy: Adaptation communication strategies of the Kasepuhan Citorek comunity in the Bayah Dome Geopark - Dewi Sad Tanti; Irmulansati Tomohardjo; Mochamad Taufiq Hidayat; Burhanuddin Mujtaba; Darwis Sagita (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
The Kasepuhan Citorek Indigenous Community preserves natural equilibrium through its unique agriculture techniques. The establishment of the Bayah Dome Geopark Program offers hope for sustainable tourism, but it also raises worries about disrupting the previously preserved environmental balance. This research investigates the Citorek community's response to policy and environmental changes using the ideas of development communication, participation, adaptation communication, and populism. The case study technique, which includes in-depth interviews and participant observation, exposes a populist narrative from the government or local elites about the geopark. Collaboration among the government, academics, and local people is critical to sustainable geopark development, with social capital and community engagement playing major roles. The key proposal is to improve the synergy of local-national policy and promote tourism that protects environment and culture.